PRAKTIK KEUANGAN SOSIAL ISLAM DI NEGARA MUSLIM - Retnawati Siregar; Marliyah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Islamic Social Financial Institutions are now a global phenomenon marked by the increasing number of Islamic Social Financial Institutions that provide positive impact benefits, and have played an important role in the economy of a country and in the benefit of the people. The purpose of this research is to analyze Islamic social finance practices in Muslim countries. This research method uses library research and uses descriptive analysis. The findings show that the most well-known practice of Islamic social finance, namely ZISWAF (zakat, infaq, shodaqoh, waqf) is used as an alternative means of alleviating poverty and assisting in the welfare of the ummah, not only in Indonesia but globally, especially in Muslim countries.